(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Xerostomia, or dryness in mouth is usually concerned with decrease in the amount of saliva flow causing severe discomfort to the patients. As saliva is the most beneficial fluid which play a very important role in the sensation of flavour perceived in the mouth and lubrication of tongue. Along with this it also contributes in defending of the oral mucous membranes by providing bactericidal action such as proteolytic enzymes, lysozyme, lacto-peroxidase and IgA, IgG antibodies.The significant risk factors for xerostomia may be systemic or be iatrogenic– demonstrated by many types of pharmacologically active agents or chemotherapy, ionized radiation which is used as adjuvant in destroying malignant cells and aging issues. The related syndrome to this group include Sjogren’s syndrome manifested primarily by lacrimal and salivary glands inflammation producing various clinical symptoms. This is a typical problem for diabetes patients which is correlated with inadequate salivary flow followed by alterations in the microcirculation. Several treatment strategies for the management of such condition include medications for lubrication of mucosa and saliva substitutes. But, understanding the primary cause of xerostomia enables quicker diagnosis and a most effective treatment strategy. The intent of this article is to briefly review the etiology of xerostomia along with risk factors.